2022
DOI: 10.1002/bies.202200150
|View full text |Cite
|
Sign up to set email alerts
|

Cell growth and the cell cycle: New insights about persistent questions

Abstract: Before a cell divides into two daughter cells, it typically doubles not only its DNA, but also its mass. Numerous studies in cells ranging from yeast to mammals have shown that cellular growth, stimulated by nutrients and/or growth factor signaling, is a prerequisite for cell cycle progression in most types of cells. The textbook view of growth‐regulated cell cycles is that growth signaling activates the transcription of G1 Cyclin genes to induce cell proliferation, and also stimulates anabolic metabolism and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 132 publications
0
6
0
Order By: Relevance
“…Cellular growth is indispensable for cell-cycle progression across various cell types, but the intricate molecular mechanisms bridging these fundamental cellular processes remain not fully elucidated (66). We observed that reducing CDK8 or CycC in wing discs increased the S-phase cell population, and ultimately leading to more but smaller cells in adult wings (38).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular growth is indispensable for cell-cycle progression across various cell types, but the intricate molecular mechanisms bridging these fundamental cellular processes remain not fully elucidated (66). We observed that reducing CDK8 or CycC in wing discs increased the S-phase cell population, and ultimately leading to more but smaller cells in adult wings (38).…”
Section: Discussionmentioning
confidence: 99%
“…KEGG pathway enrichment analysis results showed that high-concentration retinoic acid treatment (TG1) specifically activated the cell cycle, ferroptosis, glycine, serine and threonine metabolism, and other signaling pathways. In addition to the glycine, serine, and threonine metabolism mentioned above and the cell activity-related pathways, promoting the cell cycle [50] and ferroptosis resistance [51] are also important ways to promote cell proliferation and improve cell vitality.…”
Section: Discussionmentioning
confidence: 99%
“…In unicellular free-living eukaryotes, cell growth is largely limited by nutrient availability, while dedicated cell-autonomous mechanisms sense cell size and transmit this signal to control division. [12][13][14] For multicellular organisms, in order to maintain tissue architecture and sustain the proper distribution of cell types, both cell growth and division processes are thought to be controlled extrinsically by extracellular signals. 13,15 However, it is unclear how these signals are linked within a single cell to coordinate its growth and division to maintain a constant cell size.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] For multicellular organisms, in order to maintain tissue architecture and sustain the proper distribution of cell types, both cell growth and division processes are thought to be controlled extrinsically by extracellular signals. 13,15 However, it is unclear how these signals are linked within a single cell to coordinate its growth and division to maintain a constant cell size. In adult stem cells that continually grow and divide, cell size affects critical stem cell functions like niche interactions, fate-specification, and tissue regeneration capacity.…”
Section: Introductionmentioning
confidence: 99%